On one question of B. Amberg - Sysak, Ya. P. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
In the case where a group G is the product G = AB of Abelian subgroups A and B, one of which has і finite 0-rank, it is proved that the Fitting subgroup F and the Hirsch - Plotkin radical R admit the lecompositions F = (F A)(F B) and R = (R A)(R B), respectively. This gives the affinitive answer to B. Amberg’s question.